2013
DOI: 10.1002/jccs.201200595
|View full text |Cite
|
Sign up to set email alerts
|

A Reusable Palladium(II)/Cationic 2,2′‐Bipyridyl Catalytic System for Hydroxycarbonylation of Aryl Iodides in Water

Abstract: A water‐soluble palladium(II)/cationic 2,2′‐bipyridyl system was utilized to catalyze hydroxycarbonylation of aryl iodides in the presence of a pressurized CO atmosphere under a basic aqueous solution at 100 °C. The residual aqueous solution could be reused in several times with only a slight decrease in catalytic activity. Thus, it reduced wastage of the precious metal in the reaction. A variety of aromatic carboxylic acids could still be obtained in high yields with the catalytic amount to 0.01 mol%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…While Figure 11B uses methyl sulfonyl chloride where Figure 11A uses fluoro sulfonyl fluoride, both reagents are halogenated sulfonyl compounds. Figure 11C (Josyula and Mitesh, 2014) and Figure 11D (Tsai et al, 2013;Han et al, 2015;Mallia et al, 2016) shows four more cases the model conclusively labeled correctly. The performance for the cases in Figure 11E varies again, with the first two being labeled correctly Monteiro et al, 2016).…”
Section: Resultsmentioning
confidence: 90%
“…While Figure 11B uses methyl sulfonyl chloride where Figure 11A uses fluoro sulfonyl fluoride, both reagents are halogenated sulfonyl compounds. Figure 11C (Josyula and Mitesh, 2014) and Figure 11D (Tsai et al, 2013;Han et al, 2015;Mallia et al, 2016) shows four more cases the model conclusively labeled correctly. The performance for the cases in Figure 11E varies again, with the first two being labeled correctly Monteiro et al, 2016).…”
Section: Resultsmentioning
confidence: 90%
“…We recently reported that cationic 2,2′-bipyridyl is an excellent ligand to bring PdCl 2 (NH 3 ) 2 into the aqueous phase, in order to efficiently perform several carbon–carbon bond-formation reactions, and the residual aqueous solution can be reused for the next run [58,59,60,61,62,63]. As part of our continuing efforts in the development of water-soluble and reusable catalytic systems for carbon–carbon bond-forming reactions, we report, herein, on a reusable PdCl 2 (NH 3 ) 2 /cationic 2,2′-bipyridyl catalytic system, which can be applied for Stille coupling of aryl halides with organostannanes in water under aerobic conditions, in the presence of NaHCO 3 as a base.…”
Section: Introductionmentioning
confidence: 99%